Appropriateness of psychotropic medication use in a cohort of adolescents with intellectual disability in Queensland, Australia. Issue 6 (17th November 2020) - Song, Menghuan; Ware, Robert S.; Doan, Tan N.; McPherson, Lyn; Trollor, Julian N.; Harley, David
Abstract : Background: Psychotropic medications are sometimes used off-label and inappropriately. This may cause harm to adolescents with intellectual disability. However, few studies have analysed off-label or inappropriate prescribing to this group. Aims: To examine the appropriateness of psychotropic prescribing to adolescents with intellectual disability living in the community in south-east Queensland, Australia. Method: Off-label medication use was determined based on whether the recorded medical condition treated was approved by the Australian Therapeutic Goods Administration. Clinical appropriateness of medication use was determined based on published guidelines and clinical opinion of two authors who specialise in developmental disability medicine (J.N.T. and D.H.). Results: We followed 429 adolescents for a median of 4.2 years. A total of 107 participants (24.9%) were prescribed psychotropic medications on at least one occasion. Of these, 88 (82.2%) were prescribed their medication off-label or inappropriately at least once. Off-label or inappropriate use were most commonly associated with challenging behaviours. Conclusions: Off-label or inappropriate use of psychotropic medications was common, especially for the management of challenging behaviours. Clinical decision-making accounts for individual patient factors and is made based on clinical experience as well as scientific evidence, whereas label indications are developed for regulatory purposes and, although appropriate at a population level, cannot encompass the foregoing considerations. Education for clinicians and other staff caring for people with intellectual disability, and a patient-centred approach to prescribing with involvement of families should encourage appropriate prescribing. The effect of the National Disability Insurance Scheme on the appropriateness of psychotropic medication prescribing should be investigated.